Seeking Positive Strengths in Buffering Athletes’ Life Stress–Burnout Relationship: The Moderating Roles of Athletic Mental Energy - Chiou, Shiow-Shya; Hsu, Yawen; Chiu, Yi-Hsiang; Chou, Chien-Chih; Gill, Diane L.; Lu, Frank J. (Frontiers in Psychology, 2020)
In search of positive strengths that bolster athletes’ reaction to stress, the purpose of this study was to examine the moderating effects of athletic mental energy on the athletes’ life stress–burnout relationship. This study recruited two samples (Study 1 = 230; Study 2 = 159) and administered the College Student-Athlete’s Life Stress Scale (CSALSS; Lu et al., 2012), Athletic Mental Energy Scale (AMES; Lu et al., 2018), and Athlete Burnout Questionnaire (ABQ; Raedeke and Smith, 2001). Two separate hierarchical multiple regression analyses found that the emotional and cognitive components of athletic mental energy moderated the athletes’ life stress–burnout relationship across the two studies. Results provided the initial evidence that athletic mental energy can be positive strengths in buffering the stress–burnout relationship. Theoretical implications, limitations, practical applications, and future research directions are discussed.